Kerajaan Allah sebagai Landasan bagi Relasi antara Gereja dan Dunia dalam Teologi Wolfhart Pannenberg - Haward, Ambrosius Setiadvento (STFT Jakarta, Indonesia, 2021)
Wolfhart Pannenberg understood the eschatological dimension as an essential element in the discourse of the Kingdom of God. Unfortunately, this critical element is often missing in theological discourses in general that limit the theme of the Kingdom of God in the context of the end of time and disconnect it from everyday human life. This work aims to explain Pannenberg’s thoughts about the Kingdom of God, which is an eschatological realityand closely related to Christian participation in the world. The author argues that Pannenberg understood the Kingdom of God as a foundation for the church and that the hope for the realization of God’s Kingdom urged the church to embody the values of God’s Kingdom by engaging actively with the world today.